A Continuously Differentiable Turbine Layout Optimization Model for Offshore Wind Farms. (September 2016) - Klein, Arne
Abstract: This article presents a continuously differentiable modification of the commonly used Jensen wake model. This property is con- served in the wake combination model and, by formulating the turbine's power curve as a set of constraints, also in the computation of a turbine's power output. The resulting objective function, maximizing the total power production, and optimizing the turbine positions, is thus continuously differentiable, and gradient based solution methods can be applied. Numerical experiments are conducted with simulated wind data of six offshore wind farm locations.